President Houari Boumediene and the 1967 War - ben abderrahmane, hichem (The Algerian Historical Journal, 2026)
This article reviews President HouariBoumediene's interaction with the 1967 war, also known as the Naksa War. It examines the causes, stages, results, and repercussions of the war on the Arab region. The loss of large areas of land by the frontline states prompted other Arab governments to attempt to provide assistance. Among these countries is Algeria, represented by its president, HouariBoumediene. Despite the near-rupture with Egypt since his coup against Ahmed Ben Bella in 1965, he overcame this and put the interests of the Arab nation above his own, supporting the Egyptian front and participating with the National People's Army in the battle from the beginning. The article touches on the Algerian army's participation in the War of Attrition and supporting Egyptian forces in attacks against Israeli positions. This gave Algeria an important role on the Arab scene in general and in the Arab conflict in particular, despite its recent independence.